The “atrial dancing”: echocardiographic diagnosis of electrocardiographic query - Siniscalchi, Carmine; Gaibazzi, Nicola (Acta Biomedica Atenei Parmensis, 2015)
The direct observation of the cardiac structure through the echocardiographic exam offers, in some cases, the advantage to resolve difficult diagnostic definition. In this paradigmatic case we emphasize as an accurate observation of the echocardiographic figures and movies can resolve also an electrocardiographic query.